Penguatan Moderasi Beragama Pada Siswa Pasraman di Kota Mataram - I Wayan Rudiarta (Jayapangus Press, 2023)
This study aims to conduct an analysis related to efforts to strengthen awareness of religious moderation in pasraman students in Mataram City. This research is based on the occurrence of several ripples of conflict with religious nuances in Lombok Island, including those that have occurred in the city of Mataram. Anticipating this, education as a vehicle for developing knowledge and values ​​for students has a central position. Education, including non-formal education, must contribute to strengthening the awareness of religious moderation to students. One of the non-formal education developed by the Hindu community is pasraman. This study uses a descriptive qualitative approach, with data collection using observation techniques, interviews and documentation. The data that has been obtained is then analyzed by data reduction, data verification, and conclusions drawing. Research findings show that in the city of Mataram there are 21 pasraman that carry out learning by emphasizing the values ​​of intimacy and based on local wisdom. Learning that takes place in a simple and friendly manner is one of the assets in an effort to strengthen religious moderation for students. The form of strengthening religious moderation is carried out by cognitive, affective and psychomotor. Cognitive reinforcement is done by providing the core materials of Hinduism so as to build human values. Affective reinforcement is done by building attitudes based on peace (śama), self-control (dama), asceticism (tapas), chastity (śaucaṁ), tolerance (kṣānti), honesty (ārjawaṁ), knowledge (jñānaṁ), wisdom (vijñānam), and obedient to religious principles (āstikyaṁ). While psychomotor reinforcement is carried out by practicing religious skills, which include dance exercises, percussion exercises, yoga exercises, dharma gita exercises, and Balinese script exercises supported by the provision of rewards and punishments.